Study on the Geo-Stress Loading and Excavation Unloading Devices of the Large-Scale Photoelastic Model Test for Deep-Buried Tunnels. (31st August 2021) - Guo, Jiaqi; Zhu, Binzhong; Liu, Xiliang; Luo, Jing; Li, Zhaoyuan
Abstract : At present, theoretical analysis, numerical simulation, and other methods cannot be used to properly solve the problems associated with the stability and bearing capacity of the surrounding rock and its supporting system, the interaction between the supporting structure and surrounding rock, and the sharing role of each supporting structure, all of which commonly occur in deep tunnels. The model test method represented by the photoelastic test is still an important approach to study this kind of problem. In view of the deficiency of the current loading system of the photoelastic model test, we developed a geo-stress loading system for the photoelastic model test, which can simulate the in situ geo-stress environment of unidirectional loading, bidirectional equal pressure, bidirectional unequal pressure, and tridirectional unequal pressure. The universal retaining force loading rod can realize the stability and effective compensation of loading, which is an original design. According to the principle of umbrella-shaped expansion and contraction mechanism, an excavation unloading device for the photoelastic model test is developed, which can realize the simulation of various degrees of displacement release in the excavation process of deep tunnels and other underground projects. The loading simulation test and excavation unloading simulation test show that the geo-stress loading system and excavation unloading device developed in this paper are flexible, exhibit good performance, and can fully achieve their respective test functions. The combination of two devices can compensate for the insufficiency of the current photoelastic model test and will promote the application of photoelastic model tests in underground engineering applications such as deep tunnel projects.